Comparison of Two Different Accelerated Corneal Cross-linking Procedures Outcomes in Patients with Keratoconus - Özülken, Kemal; Yüksel, Erdem; Kıızltoprak, Hasan; Aydemir, Emre; Aksoy Aydemir, Gözde (AVES Publishing Co., 2020)
Corneal cross-linking treatment is the unique treatment method that can cease the progression of keratoconus disease. Because of the long duration of conventional treatment, accelerated cross-linking treatment methods are being developed.To compare two different accelerated corneal cross-linking protocols in terms of postoperative visual acuity and topographic findings (higher-order aberrations and keratometry values).Retrospective comparative study.Sixty-five eyes of 43 patients (30 men and 13 women) who underwent two different accelerated corneal cross-linking protocols (10 min, 9 mW/cm2 and 5 min, 18 mW/cm2) for progressive keratoconus were retrospectively analyzed. Patients were divided into two groups according to the accelerated corneal cross-linking treatment protocol: group 1 (10 min, 9 mW/cm2, 32 eyes of 21 patients) and group 2 (5 min, 18 mW/cm2, 33 eyes of 22 patients). Uncorrected visual acuity and best-corrected visual acuity values and topographic findings (central corneal thickness and flat and steep keratometry values) were recorded preoperatively and 6 months after corneal cross-linking treatment. High-order aberration values measured with Pentacam preoperatively and 6 months after corneal cross-linking were also recorded.In both groups, a significant improvement was detected in the uncorrected visual acuity and best-corrected visual acuity levels preoperatively and 6 months postoperatively (group 1: p=0.001, p=0.001 and group 2: p=0.001, p=0.001, respectively). In addition, central corneal thickness values decreased significantly in both groups (p=0.006 and 0.001). Trefoil values showed no significant difference preoperatively and 6 months postoperatively in group 1 (p=0.160 and 0.620, respectively). In groups 1 and 2, coma values were found to decrease significantly in the 6th postoperative month compared with preoperative values (p=0.001 and 0.020, respectively). There was no significant difference between preoperative and 6th month postoperative horizontal and vertical trefoil values in both groups (p=0.850 and 0.140, respectively). There was no significant difference between the two groups in terms of preoperative and 6th month postoperative higher-order aberrations, refractive errors, keratometry values, and uncorrected visual acuity and best-corrected visual acuity levels.Both accelerated corneal cross-linking procedures provide similar improvement in topographic findings, coma values and visual acuity.
Keywords: accelarated cross-linking; Adult; Male; higher-order aberations; corneal cross-linkin; Adolescent; keratoconus; R; Visual Acuity; Accelarated cross-linking; coma; cxl; Keratoconus; Cornea; cx1; Outcome Assessment, Health Care; Medicine; Humans; Original Article; Female; Retrospective Studies; 3. Good health